Esthetic and didactic considerations for literature teaching: as historical-dialetic materlistic apropriation of João Cabralde Melo Neto - Nardy, Joao Pedro [UNESP]; Teixeira, Lucas Andre [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2021)
Is the poetry of Joao Cabral de Melo Neto with its place assured in the current educational programs about literature teaching? Departing since a radical criticism about the state of art in pedagogics, it is considered that no. The current tendency today tends to discard it along with other precious literary productions, within a larger process of emptying of scholar contents. Why the valorization of poetry requires a substantive, historical and critical pedagogy theory? And why is Joao Cabral's poetry relevant for an emancipating and critical education perspective? In other words, this paper underlines the importance of Historical-critical Pedagogy for educators and scholars of Joao Cabral, by one way; and the importance of Joao Cabral for educators that assume such the PHC as other critical perspectives in education, by another way. To solve this problem, the paper analyses the poem The River, and discuss the esthetic reflection theory, by Gyorgy Lukacs, as well the Activity Theory, by A. Leontiev, considered opportune for the problem of the directive or non-directive way of the educational work and its needs. These are existing questions in the pith of the current pedagogic problematics.
Keywords: Literature teaching; Joao Cabral; Historical-critical pedagogy; Activity theory; Esthetic reflection; Learning to learn